Slightly acidic electrolyzed water inhibits inflammation induced by membrane vesicles of Staphylococcus aureus - Shimamura, Yuko; Oura, Yukino; Tsuchiya, Madoka; Yamanashi, Yuka; Ogasawara, Asako; Oishi, Minami; Komuro, Misaki; Sasaki, Kuniaki; Masuda, Shuichi (Frontiers in Microbiology, 2024)
Staphylococcus aureus grows in the skin of patients with atopic dermatitis and the associated symptoms are induced by membrane vesicles (MVs). This study explored the effects of slightly acidic electrolyzed water (SAEW) on the expression of virulence factors of S. aureus and MV-induced inflammation to uncover the potential of SAEW as a new treatment method for atopic dermatitis. Expression levels of genes related to virulence factors in S. aureus was assessed and S. aureus-derived MVs were characterized. Moreover, expression level of MV-induced Type I allergic reaction-related genes in RBL2H3 cells was also assessed. Significantly decreased staphylococcal enterotoxin A production and decreased virulence factor-related gene expression were observed after culturing S. aureus in broth supplemented with SAEW at ratios of 1, 2, and 5 per broth. MVs prepared by culturing S. aureus in SAEW-supplemented broth exhibited altered particle size and markedly reduced staphylococcal enterotoxin A content under all addition conditions; moreover, those obtained at a ratio of 1:5 (broth:SAEW) exhibited a reduction in the expression of several proteins associated with hemolytic activity and free iron uptake. The MVs prepared in SAEW-supplemented broth also exhibited remarkably reduced allergy-related gene expression levels in rat cell lines derived from basophilic leukemia-2H3 cells. Overall, SAEW is expected to suppress atopic dermatitis symptoms through the alteration of the properties of S. aureus-derived MVs.